2010
DOI: 10.1143/jjap.49.085001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Heat Transport in a Nanoribbon by the Thermal Wave at Different Durations of Pulse Heating

Abstract: In recent year, progress has been made in the study of ballistic heat flow and phonon scattering by phonon spectroscopy and phonon-imaging techniques. Regarding the femtosecond laser application to nanostructures, phonon generation in nanoscale electronics is the focus of interest in the investigation of the mechanism of thermal wave formation at different heating pulses and conditions for heat flux propagation in nanostructures. We test an atomic model of thermal transport in a nanoribbon after a few picoseco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…In the simplified MD model of a nanoribbon that we consider, without coupling to the electronic state, our system relates to the ground electronic state and non-resonant phonon generation. In our case, it is confirmed that the MD simulation alone is able to reproduce the coherent phonon generation and propagation in the anharmonic LJ potential of a nanoribbon with simultaneously present diffusive modes (13) .…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…In the simplified MD model of a nanoribbon that we consider, without coupling to the electronic state, our system relates to the ground electronic state and non-resonant phonon generation. In our case, it is confirmed that the MD simulation alone is able to reproduce the coherent phonon generation and propagation in the anharmonic LJ potential of a nanoribbon with simultaneously present diffusive modes (13) .…”
Section: Introductionsupporting
confidence: 77%
“…The model was generalized by the nondimensional calculations using Lennard-Jones (LJ) potential. The Ar atoms are calculated, with potential parameters in the LJ potential being given (15) , details can be found in the Appendix (13) . The atoms in the calculation region were represented by Ar.…”
Section: Model and Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonequilibrium MD, or the direct method, mimics the heat source and sink in experiment, and then uses Fourier's law to quantify the thermal conductivity, nonetheless, only applies to diffusive heat conduction at steady-state [35][36][37]. In the past decades, a few attempts have been made to study the transient heat pulse propagation using MD thermostats to model the heat pulses [38][39][40][41]. However, thermostat algorithms thermalize phonons and tend to destroy phonon coherency [42], and hence are not suited for the simulation of the coherent phonon excitation by ultrafast laser pulse experiments.…”
Section: Methodology and Verification 21 The Phonon Representation Omentioning
confidence: 99%
“…Unfortunately, neither method is well suited for the simulation of the generation and propagation of a phonon pulse. Existing attempts to study the transient heat pulse propagation have used the thermostat algorithms to model the heat source [33][34][35]. However, thermostat algorithms mimic thermalizing events such as damping and dephasing of phonon waves.…”
Section: Introductionmentioning
confidence: 99%